Pengaruh Masuknya Budaya Populer terhadap Eksistensi Ajaran Sedulur sikep pada Masyarakat Samin - Ken Widyatwati (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Klopoduwur Blora  villagers are mostly descendants of Samin Surosentiko is a society that is still running the egalitarian values in daily life. These groups are known as community Samin. Samin community is a community that is consistent in behavior among others uphold the values of honesty , not envy, jealousy , prejudice is not ugly to others , behave and act what is ( not making this up ). Samin important for society not to disturb others and vice versa Samin people also do not want to disturb other people 's life and social institutions. Samin society is a society that can integrate the influx of popular culture with the attitude and teachings Sedulur sikep . Sedulur sikep teachings on society Samin persist accordance with the portions although popular culture spere  entered public life Samin. In everyday life people Samin uphold the teachings Saminisme entrenched . Samin society trying to keep the existence and preserve the culture and teachings Sedulur sikep to instill and teach the younger generation descendants and tribes Samin.